Answer:
[tex]y = -3[/tex]
[tex]x = -2[/tex]
Step-by-step explanation:
Given
[tex]-9x + 4y = 6[/tex]
[tex]9x + 5y = -33[/tex]
Required
Find x and y
To eliminate x, we simply add both equations
[tex]-9x = 9x + 4y + 5y= 6 - 33[/tex]
[tex]9y= -27[/tex]
Divide by 9
[tex]y = -27/9[/tex]
[tex]y = -3[/tex]
Substitute -3 for y in [tex]9x + 5y = -33[/tex]
[tex]9x + 5 * -3 =-33[/tex]
[tex]9x - 15 =-33[/tex]
Add 15 to both sides
[tex]9x =-15 -33[/tex]
[tex]9x =-18[/tex]
Divide by 9
[tex]x = -18/9[/tex]
[tex]x = -2[/tex]